2020
DOI: 10.1021/acssensors.0c00050
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based Device for Naked Eye Urinary Albumin/Creatinine Ratio Evaluation

Abstract: This paper introduces the concept of “Drawing-PADs” (Drawing paper-based microfluidic analytical devices) allowing to intuitively evaluate the urinary albumin (Alb) index, a clinically important parameter used for the early detection of renal deficiencies related to diabetes, among others. To enable regular monitoring of the Alb index, a simple examination method suitable for self-diagnosis is highly desirable. The Drawing-PADs rely on the simultaneous naked eye detection of Alb and creatinine (Cre) on a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…This method is based on a staining protocol based on the use of: (i) Fast Blue BB (0.12%) dye to stain the (pseudo-) esterase activity of HSA both on agarose and Native PAGE; (ii) 2-naphthyl acetate, an ester substrate of HSA, and (iii) neostigmine, a selective acetyl-cholinesterase inhibitor [ 123 ]. This method could find application in either HSA pharmaceutical preparation (e.g., to check adulteration of human milk with cow milk) [ 123 , 124 , 125 ] or in diagnostic detection (e.g., to highlight the (pseudo-)esterase activity of HSA in urine representing a sign of microalbuminuria) [ 123 , 126 ].…”
Section: Hsa Enzymatic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is based on a staining protocol based on the use of: (i) Fast Blue BB (0.12%) dye to stain the (pseudo-) esterase activity of HSA both on agarose and Native PAGE; (ii) 2-naphthyl acetate, an ester substrate of HSA, and (iii) neostigmine, a selective acetyl-cholinesterase inhibitor [ 123 ]. This method could find application in either HSA pharmaceutical preparation (e.g., to check adulteration of human milk with cow milk) [ 123 , 124 , 125 ] or in diagnostic detection (e.g., to highlight the (pseudo-)esterase activity of HSA in urine representing a sign of microalbuminuria) [ 123 , 126 ].…”
Section: Hsa Enzymatic Propertiesmentioning
confidence: 99%
“…During its long lifetime, HSA molecule makes about 15,000 passes through the circulation [ 1 ] undergoing damages that impairs its ligand binding and anti-oxidant properties [ 4 , 126 ]. The HSA anti-oxidant activity depends on: (i) the reactivity of the Cys34 residue, which in turn is affected by chemical modifications (e.g., oxidation and cysteinylation), (ii) post-translational modifications like glycation, (iii) FAs binding, and (iv) aging.…”
Section: Hsa Enzymatic Propertiesmentioning
confidence: 99%
“…As a result, the effective treatment period is curtailed, leading to serious lesions and a significant deterioration in quality of life [104]. However, recent research has shown that lab-on-paper platforms provide a feasible means of detecting early-stage kidney disease by evaluating the concentrations of creatinine (Cre) and albumin (Alb) [105][106][107][108][109][110][111], micro-albumin and protein [112][113][114][115][116], and uric acid [117][118][119][120][121][122][123] in urine samples.…”
Section: Creatinine Albumin Protein and Uric Acid Analysismentioning
confidence: 99%
“…The urine Alb to Cre ratio can also be used as a screening strategy for kidney disease [109]. Hiraoka et al [110] developed a Drawing lab-on-paper device for urinary Alb-to-Cre ratio analysis to support the early detection of renal insufficiency. In the proposed device, the Alb-to-Cre ratio was determined simply by drawing a straight line between the top of the two color-changed assay channel sections (Alb and Cre) and then observing the position of the intercept point on an Alb-to-Cre scale placed between them.…”
Section: Creatinine Albumin Protein and Uric Acid Analysismentioning
confidence: 99%
“…The electrochemical sensor was also integrated into a diaper and used for the detection of UA in arti cial urine. The arti cial urine solution was prepared as described in a previous report (Hiraoka et al 2020) with UA concentrations (1-3 mM).…”
Section: Sample Collection and Sample Preparationmentioning
confidence: 99%